The change on partner's behaviour after a specific time / Nur Irsya Alia Ahmad Shakir, Nur Adila Abdul Yazid and Muhammad Dannish Farish Mohamad Nasir - Ahmad Shakir, Nur Irsya Alia; Abdul Yazid, Nur Adila; Mohamad Nasir, Muhammad Dannish Farish (Faculty of Communication & Media Studies, 2021)
A person can change his or her behaviour based on how others or their partner treat them. The aim of this study is to determine the level of factors that contribute to the changes of a partner's behaviour after a specific time and the level of emotional effect in a partner's behavior change. The theory that we are using as a guide for this research is Social Exchange Theory by George Caspar Homans (1958). The study involved 402 respondents from various backgrounds by using Google Form platform. There are five elements designed in the research to measure the change in a partner's behaviour after a specific time which is religion, education, social origins, finance and habits and routine. The result shows that finance contributes the most factor of change in a partner's behaviour after a specific time. (M=3.28).